2003
DOI: 10.1139/x03-006
|View full text |Cite
|
Sign up to set email alerts
|

Short-term impacts of partial cutting on lichen retention and canopy microclimate in an Engelmann spruce – subalpine fir forest in north-central British Columbia

Abstract: The retention of canopy lichens (Alectoria, Bryoria, and foliose) in group selection (GS) and single-tree selection (STS) partial cuts (30% removal) was studied within a subalpine spruce–fir forest (Picea englemannii Parry ex Engelm. – Abies lasiocarpa (Hook.) Nutt.) in north-central British Columbia. Baseline canopy lichen loading (preharvest and immediate postharvest) was compared with lichen loading 2 years after harvesting, using both ground- and canopy-based sampling techniques. Additionally, canopy micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 18 publications
5
30
0
Order By: Relevance
“…A second response pattern that might be anticipated in lichens growing at the forest edge is that of reduced net annual growth due to reduction in the amount of time that thalli are hydrated. The increased insolation exposure and greater convection near stand edges should each contribute to the more rapid drying of lichen thalli after precipitation events as has been reported for alectorioid lichens exposed to edges of small forest openings (Coxson et al, 2003). Although this phenomenon undoubtedly occurred in both large and small thalli of L. pulmonaria placed at forest edges in the current study, increased exposure to light likely compensated for any reduction in the amount of time thalli were hydrated, at least for large thalli.…”
Section: Discussionsupporting
confidence: 60%
“…A second response pattern that might be anticipated in lichens growing at the forest edge is that of reduced net annual growth due to reduction in the amount of time that thalli are hydrated. The increased insolation exposure and greater convection near stand edges should each contribute to the more rapid drying of lichen thalli after precipitation events as has been reported for alectorioid lichens exposed to edges of small forest openings (Coxson et al, 2003). Although this phenomenon undoubtedly occurred in both large and small thalli of L. pulmonaria placed at forest edges in the current study, increased exposure to light likely compensated for any reduction in the amount of time thalli were hydrated, at least for large thalli.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, the close alternation of lichen propagule sources with regularly recruited host trees in the regeneration strata is likely to maintain high and regular lichen productivity in uneven-aged, managed forests. Such results support Dettki and Esseen (1998) and Coxson et al (2003) conclusions that, although negative impacts are sometimes observed, partial cutting should be preferentially chosen over clearcutting in order to maintain macrolichen communities most similar to natural forests.…”
Section: Immediate Effectssupporting
confidence: 82%
“…They were unable, however, to attribute this loss to the treatment since the control exhibited the same pattern. A trend consistent with that of Coxson et al (2003) suggested a greater decline in standing crop of canopy lichens in the single-tree selection area. Our results suggest that the uneven-aged group-selection cut maintained more favourable environmental conditions for lichen retention than the partial cut.…”
Section: Immediate Effectssupporting
confidence: 66%
“…On the other hand, changes in light availability at lower levels of retention indicate that small increases in canopy cover can yield large reductions in light. If sensitivity to excess solar radiation dictates biological responses (Svenning, 2000;Coxson et al, 2003;Fenton and Frego, 2005), small changes in canopy retention could yield large effects.…”
Section: Management Implicationsmentioning
confidence: 99%